Acute pancreatitis after percutaneous insertion of metallic biliary stents in patients with unresectable pancreatic cancer. Issue 1 (January 2020) - Kim, E.T.; Gwon, D.I.; Kim, J.W.; Ko, G.-Y.
Abstract : AIM: To investigate the incidence and clinical characteristics of acute pancreatitis following percutaneous insertion of metallic biliary stents in patients with unresectable pancreatic cancer. The clinical efficacy of metallic stent insertion was also evaluated. MATERIALS AND METHODS: Data from 143 patients (75 men, 68 women; mean age, 65.8 years; range, 35–88 years) with unresectable pancreatic cancer who underwent percutaneous metallic biliary stent insertion between March 2007 and December 2017 were evaluated retrospectively. The incidence and clinical characteristics of acute pancreatitis were analysed. Stent patency and patient survival rates were calculated by Kaplan–Meier analysis. RESULTS: Technical success was achieved in all patients. Among 31 patients with serum amylase levels above normal values (30–110 U/l), only nine had symptoms of acute pancreatitis (incidence, 6.4%). No statistically significant risk factors were identified. Pancreatitis was successfully managed with conservative treatment at a mean of 2.9 days (range, 1–4 days). The median stent patency and patient survival times were 117 days (95% confidence interval [CI], 87–148 days) and 150 days (95% CI, 125–174.9 days), respectively. CONCLUSIONS: Acute pancreatitis was a relatively rare complication after percutaneous insertion of metallic biliary stents in patients with unresectable pancreatic cancer, and no significant risk factors were identified. Therefore, insertion of metallic biliary stents was seen to be a feasible and effective treatment approach in this patient group. Highlights: Following the insertion of metallic biliary stents in patients with pancreatic cancer, the incidence of pancreatitis is relatively low. No significant risk factors associated with pancreatitis following the insertion of metallic biliary stents were identified. Insertion of percutaneous biliary stents is feasible and effective palliative therapy.